COMMITMENT DEGREE OF JARASH UNIVERSITY ADMINISTRATION TO THE ACADEMIC PERFORMANCE ETHICS - Badah, Ahmad M.; Alaoamlh, Habis; Alsaleem, Bashar; Al-Ali, Yosra (European Scientific Journal, ESJ, 2013)
ï»¿This study aimed at knowing the degree of commitment to the criteria of Academic Performance Ethics at the Administration of Jerash University. In order to realize this, an instrument has been developed to measure the degree of commitment to the criteria of academic performance ethics at the administration of Jerash University from the teaching faculty point of view. The study consists of 36 items with suitable validity and consistency, then they were distributed to a sample consists of 142 staff members during the second semester 2010/2011 at Jerash University- Jordan. The results of the study revealed that the degree of commitment to the criteria of academic performance ethics at the administration of Jerash University was high. Besides, it showed that there were statistically significant differences in the evaluation of the sample members due to the college specialty variable, and to the behalf of humanity colleges, but there were no statistically- significant difference to the years of experience variable. The study recommended that Jordan Universities should prepare a guide to the ethics of the academic performance system to be used as a basic reference to determine the relationship between the university administration, teaching staff, and students, as one team work.